Daily life strategies of Polish farmers - Drąg, Zbigniew (Sociology of rural worlds in Poland and France: field research and studies, 2024)
The article raises the issue of the quality of life of Polish farmers in the context of ongoing globalization processes. Globalization brings with it new phenomena and processes that reorganize human lives and may be perceived as threats and challenges. Does the increased sense of threats and challenges of globalization worsen the quality of one’s live, defined in subjective terms as mental well-being? The author analyzes the above issue, referring to the results of a study conducted in 2017 on a representative sample of 3,551 family farmers. Mental well-being is analyzed with reference to general life satisfaction, sense of optimism, social support, and internal harmony; in turn, the threats and challenges of globalization are studied in the context of one’s work, finances, cultural life and other spheres. It turns out that an increase of threats and challenges as perceived by farmers was accompanied by enhanced mental well-being. The decisive factors here were the strategies adopted by farmers to control globalization changes: active v passive (avoidance). Assuming that knowledge about globalization threats and challenges is an important way to control them, adaptive activism (related to the disposition of actively obtaining information about new situations) was adopted as an indicator of an active strategy. In turn, recognition of emotional religiosity as an indicator of an avoidance strategy resulted from an assumption that the consequence of the inability to control changes based on a rational factor may be turning to a transcendent factor as providing hope for protection against something new and incomprehensible. Both types of responses could be used by farmers simultaneously, depending on the situation. Thanks to this, their psychological well-being has not decreased in the conditions of globalization changes.